2020
DOI: 10.1038/s41598-020-63988-4
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Physisorption Characteristics of O2 in Coal Powder are Effected by Coal Nanopore Structure

Abstract: Bo tan , Gang cheng ✉ , Xiaoman Zhu & Xianbing Yang coal is a porous medium. oxygen molecules in the air penetrate through the pores of coal and are adsorbed on the coal surface. Low-temperature oxidation of coal then occurs, by which coal spontaneous combustion is promoted. Given this process, the authors analysed the physisorption characteristics of o 2 in pulverized coal from the perspective of nanopore structure. In this study, five different kinds of coal samples (two lignites, one bituminous coal, and tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…49 In the nanopore systems, the presumed inhibitor concentration [A] o increases linearly with reciprocal pore size, as shown in Figure 2B, which indicates the importance of the pore surface area. This also is consistent with the inhibitor being oxygen and consistent with the presence of physisorbed oxygen in the nanopores, which has been reported to be as high as 0.3 mol/L for nanoporous coal 50 and as high as 0.2 to 4 mol/L for mesoporous silica. 51 The fact that the inhibitor concentration is independent of the type of matrix also suggests that functional surface groups are not a primary source of inhibition; we have found that added trimethylsilanol does increase the induction time but only by a factor of 2.4 relative to the bulk for 24 wt % trimethylsilanol (which is equivalent to the silanol concentration in an 8 nm silica pore assuming that the CPG surface is akin to a fully hydroxylated silica surface, that is, having 4.9 OH groups/nm 2 ) 52 which is considerably less the factor of 10 that is found in all of the 8 nm nanopores.…”
Section: Resultssupporting
confidence: 88%
“…49 In the nanopore systems, the presumed inhibitor concentration [A] o increases linearly with reciprocal pore size, as shown in Figure 2B, which indicates the importance of the pore surface area. This also is consistent with the inhibitor being oxygen and consistent with the presence of physisorbed oxygen in the nanopores, which has been reported to be as high as 0.3 mol/L for nanoporous coal 50 and as high as 0.2 to 4 mol/L for mesoporous silica. 51 The fact that the inhibitor concentration is independent of the type of matrix also suggests that functional surface groups are not a primary source of inhibition; we have found that added trimethylsilanol does increase the induction time but only by a factor of 2.4 relative to the bulk for 24 wt % trimethylsilanol (which is equivalent to the silanol concentration in an 8 nm silica pore assuming that the CPG surface is akin to a fully hydroxylated silica surface, that is, having 4.9 OH groups/nm 2 ) 52 which is considerably less the factor of 10 that is found in all of the 8 nm nanopores.…”
Section: Resultssupporting
confidence: 88%
“…Their results showed that the amount of adsorbed oxygen corresponds to the topological dimension of the carbon pores and the volume of coal nanopores, but inversely to the number of pores filled within the material. Besides, they have also found that the physical adsorption rate increases with an increased number of folds and surface area, and they noticed low desorption temperatures of physisorbates due to weak interactions (Tan et al, 2020). Physisorption is usually described as an exothermic reaction with low enthalpy values due to weak attraction forces from van der Waals (Shahabi and Raissi, 2016) and it can also be related to an adsorption energy.…”
Section: Physical Adsorptionmentioning
confidence: 99%
“…The spontaneous combustion of coal is actually a process of complex reactions of various groups in the structure of coal, and the process has shown good segmentation features at different temperatures; thus, a segmentation study of the oxidation process can improve its performance. The segmentation of the coal oxidation process can improve its accuracy [10][11][12]. Current research shows that the division of coal's spontaneous combustion phase is mainly based on the temperature point of CO, CO 2 , and other marker gases and the change rule of the generated gases with the temperature.…”
Section: Introductionmentioning
confidence: 99%